Atrial fibrillation and the athletic heart. (January 2015) - Redpath, Calum J.; Backx, Peter H.
<x xml:space="preserve">Abstract</x> Purpose of review Endurance exercise, despite a plethora of proven health benefits, is increasingly recognized as a potential cause of lone atrial fibrillation. Moderate exercise reduces all-cause mortality and protects against developing atrial fibrillation. However, more intense exercise regimes confer modest incremental health benefits, induce cardiac remodelling and negate some of the cardiovascular benefits of exercise. The implications of endurance exercise and athletic heart are becoming increasingly relevant as the popularity of endurance exercise has increased 20-fold within a generation. Recent findings An apparent dose–response relationship exists between endurance exercise and left atrial dilatation. Repeated strenuous endurance exercise overloads atria, resulting in stretch-induced 'microtears', inflammation and endocardial scarring. Although these findings are observational in humans, similar mechanisms have recently been confirmed in animal models suggesting causation. Summary Currently, it is not known whether a ceiling for endurance exercise exists, and, if so, what factors determine the threshold of harm. Although preliminary research is promising, much work remains if we are to understand the mechanisms underpinning atrial fibrillation in athletes.